Evaluation of Acute Kidney Injury Associated With Anticancer Drugs Used in Gastric Cancer in the Japanese Adverse Drug Event Report Database. Issue 12 (December 2019) - Uchida, Mayako; Kondo, Yuki; Suzuki, Shinya; Hosohata, Keiko
Background: Development of acute kidney injury (AKI) depends on the severity of renal dysfunction, clinical setting, comorbid factors, and geographical location. Gastric cancer is one of the deadliest malignancies worldwide, and its incidence is significantly high in Japan.Objective: We analyzed the rank-order of the association of anticancer agents for gastric cancer with AKI using a spontaneous reporting system database, the Japanese Adverse Drug Event Report database.Methods: We performed a retrospective pharmacovigilance disproportionality analysis using the adverse event reports submitted to the Pharmaceuticals and Medical Devices Agency between April 2004 and March 2017.Results: Anticancer drug-related AKI was common in patients in their 60s and 70s (39.2% and 43.2%, respectively). AKI occurred most frequently within 1 month after anticancer drug administration. The signals of AKI were reported after treatment with S-1 (tegafur/gimeracil/oteracil), cisplatin (CDDP), and capecitabine, with significant adjusted reporting odds ratios (95% CI) of 1.50 (1.09-2.07), 3.43 (2.48-4.74), and 1.82 (1.15-2.90), respectively. CDDP-induced AKI was more likely to occur in patients who were male, hypertension, or diabetes mellitus.Conclusion and Relevance: This study showed that most AKI cases were related to S-1 and/or CDDP adjuvant chemotherapy for gastric cancer treatment. The data also clarified that AKIs occurred within 1 month and that their clinical outcomes were more severe than previous reports of drug-induced AKI in general medicine. Our study provides useful information to minimize the risks of administration to patients at high risk for S-1 and/or CDDP containing chemotherapy–induced AKI.